The role of user involvement in the success, or otherwise, of system development within a major bank in South Africa - Morrison, Magda (My University, 2014)
User involvement is widely regarded as important in the development of systems. User involvement and user participation in the system development process was researched extensively since the sixties. Previous studies concentrated on various aspects of user involvement and participation and its influence on successful system implementation. Despite all these studies, the positive effect of user involvement and participation on system success has not been proven consistency. This research report examines and analyses four different system development projects in a major bank in South Africa with the objective of determining different levels of user involvement and the effect this involvement has on the success, or otherwise, of the actual systems. It also establishes an understanding of those issues regarding the involvement of users during the systems development life cycle and gives insight into the complexity of these issues. The focus is on the role users’ play in the system development and implementation, The important issues involving user contributions and objectives about expectations and expectation levels of the users and the system developers are also examined. The results stress the impact of user involvement on the development of systems. The research emphasises the role the users played in system development and implementation. Questions, such as what benefits are expected from the user involvement, what benefits will in fact be achieved and should no benefits result, the possible reasons were for the lack of achievement, will be answered. The results also provides evidence that even though a system is in use, it does not necessarily pruve to be successful and that user participation plays an important role in the SDLC.